Strategi Peningkatan Minat Baca Anak – Anak di TPA (Taman Pendidikan Al-Quran) - Widya Sastika (JURNAL PENGABDIAN KEPADA MASYARAKAT, 2013)
Reading is one of the educational activities, these can provide complex benefits, such as learning new terms or languages, science and information. Unfortunately the interest in reading  that occurs in Indonesia are alarming. Most Indonesian people gaining information is by watching television rather than reading a newspaper, magazines or even using the internet. Therefore, reading must be introduced from an early age, children are potential in building interest on reading. One of facility that provide reading for children is at TPA (Tempat Pendidikan Al Qur’an)  Al-Rahmat. In order to enhance the interest for children  to read, we are donating books for library corner at TPA Al- Rahmat Margahayu Raya, we are hoping children will not only learning the Koran itself, but can also broaden their knowledge by reading other books that has been available through our donation.